Modeling Viscosities Of Ferromanganese Slags - Kai Tang; Merete Tangstad (The Southern African Institute of Mining and Metallurgy, 2007)
The primary aim of the present investigation is to develop a model which permits to calculate/predict the viscosities of ferromanganese slags, typically focus on the MnO-SiO2-Al2O3-CaO-MgO-FeO multicomponent system. The present viscosity model emphasizes the ability of prediction, i.e. using the binary parameters to extrapolate the viscosities in ternary and higher order systems. To this end, a physical sound model is essential. Temperature dependence of viscosity is described by the Eyring?s formalism. The well-known cell model is used to define the SiO44- tetrahedra in the silicate melts. Composition dependence is expressed in term of viscous activation energy, which is characterized by the binary structural units. The viscosities in ternary and higher order systems are hence predicted using the binary activation parameters. The model has been used to calculate the viscosities in the whole liquid composition range of ferromanganese slag.